2018
DOI: 10.4018/ijcbpl.2018070102
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Usefulness of Emoticons, Emojis, and Stickers in Text Messaging

Abstract: In text-based communication, which lacks nonverbal cues, various techniques for expressing communicative intent are now available. Most prominently used are emoticons, emojis, and stickers. Although previous studies have separately examined emoticons and emojis, few have compared their features, and also included comparison with stickers. The authors conducted a survey targeting 300 Japanese young adults to investigate the features of emoticons, emojis, and stickers from the viewpoint of their perceived useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
6
0
2
Order By: Relevance
“…The differences between the two groups were significant for the perceived appropriateness of using Arabic numeral(s), hashtags, image macros, repeated punctuation marks, and videos. These findings are in line with Kato et al (2018), who reported higher ratings of emoticons, emojis, and stickers by young Japanese females than males.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The differences between the two groups were significant for the perceived appropriateness of using Arabic numeral(s), hashtags, image macros, repeated punctuation marks, and videos. These findings are in line with Kato et al (2018), who reported higher ratings of emoticons, emojis, and stickers by young Japanese females than males.…”
Section: Discussionsupporting
confidence: 90%
“…Chen et al, 2018;Shah & Tewari, 2021). In addition, Kato et al (2018) conducted a survey to investigate 300 Japanese young adults' perceptions of the usefulness of emoticons, emojis and stickers. The results confirmed an effect of gender on the participants' ratings of the usefulness of these graphical resources; specifically, women appreciated their usefulness more than men did.…”
Section: Gender Influence On Language Attitudesmentioning
confidence: 99%
“…Al-Gasawneh et al (2022) found that, in accordance with TAM, perceived usefulness and perceived ease of use are important factors that can predict consumer service usage. Kato et al (2018) suggest that the ease of transmitting emotions is the most frequently stated reason for the usefulness of emojis. Because the use of emojis in digital advertisements is still in its early stages in this country, it is important to investigate whether perceived ease of use influences perceived usefulness because of emojis in digital advertisements:…”
Section: Involvement ! Perceived Usefulnessmentioning
confidence: 99%
“…Por otra parte, los escasos estudios que sí han considerado emojis y stickers al mismo tiempo se han concentrado en variables muy específicas. Kato et al, (2018), por ejemplo, consideraron el sexo y la dependencia del teléfono móvil como variables para comparar uso de los stickers y de los emojis, factores que tienen que ver solo en parte con un posible cambio lingüístico. Por otra parte, el estudio de Konrad et al (2020), que acabamos de mencionar, se basa en datos de 2014, cuando los stickers todavía eran algo relativamente novedoso.…”
Section: La Evolución De La Comunicación Digitalunclassified